Global Agricultural Performance : Past Trends and Future Prospects - Wik, Mette (Washington, DC: World Bank, 2012)
How the production of crops and livestock products has evolved in the different regions over the past 45 years is studied. The paper focuses on how the increased supply of and demand for agricultural commodities have affected terms of agricultural trade and the sources of agricultural growth. While significant progress has been made in raising food consumption per capita (in developing countries consumption increased from an average of 2100 kcal/person/day in 1970 to almost 2700 kcal/person/day, there are still more than 850 million undernourished people worldwide. A challenge for the future is to accelerate agricultural productivity in poor countries, especially in Sub-Saharan Africa. It will also be important to satisfy increasing global demands for food, including that for animal products, sustain the natural resource base (soil, water, air and biodiversity), cope with water shortages, climate change and vulnerability, and navigate the potential conflict between devoting land to animal food and biofuels relative to direct human food.